Biscuit finds a friend - Capucilli, Alyssa Satin, 1957-; Schories, Pat (New York : HarperCollins, 1997)
A puppy helps a little duck find its way home to the pond.
80
Accelerated Reader AR
Keywords: Dogs -- Fiction; Ducks -- Fiction